2020
DOI: 10.1155/2020/1783421
|View full text |Cite
|
Sign up to set email alerts
|

Green Supplier Evaluation and Selections: A State-of-the-Art Literature Review of Models, Methods, and Applications

Abstract: The role of green supplier evaluation and selection (GSES) in supply chain management is increasingly appreciated due to the intensification of competition, raising public consciousness, and environmental issues. To improve GSES, a large number of approaches have been proposed in the past decades. However, few attempts have been made to systematically review and classify the literature in this field. The objective of this study is to afford a comprehensive review of the studies which aim to develop models and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 212 publications
0
28
0
Order By: Relevance
“…Ice and snow tourism development emphasize the protection of ice and snow tourism resources while maximizing economic benefits, while also developing and holding a variety of ice and snow tourism projects and activities, which will bring the development of ice and snow tourism to its fullest potential. Playing economic benefits at the same time, the full use of ice and snow tourism resources will inevitably reduce the abundance of ice and snow resources, the resource environment to produce huge pressure, resulting in a certain number of tourist trips down, which is a negative feedback mechanism [21]. On the other hand, the resource subsystem continuously absorbs the white waste generated during travel, leading to the destruction of the ecological environment, affecting the travel experience of tourists, and reducing the number of tourist arrivals, which is also a negative feedback mechanism.…”
Section: Gf1mentioning
confidence: 99%
“…Ice and snow tourism development emphasize the protection of ice and snow tourism resources while maximizing economic benefits, while also developing and holding a variety of ice and snow tourism projects and activities, which will bring the development of ice and snow tourism to its fullest potential. Playing economic benefits at the same time, the full use of ice and snow tourism resources will inevitably reduce the abundance of ice and snow resources, the resource environment to produce huge pressure, resulting in a certain number of tourist trips down, which is a negative feedback mechanism [21]. On the other hand, the resource subsystem continuously absorbs the white waste generated during travel, leading to the destruction of the ecological environment, affecting the travel experience of tourists, and reducing the number of tourist arrivals, which is also a negative feedback mechanism.…”
Section: Gf1mentioning
confidence: 99%
“…A PRISMA framework is frequently used in the literature [16][17][18][19][20][21][22][23] which is followed as the review methodology of this study. e referenced review studies have considered the following issues in designing their review frameworks: (1) search strategy, (2) inclusion-exclusion criteria, (3) study selection, and (4) data extraction and classification.…”
Section: Review Methodologymentioning
confidence: 99%
“…This approach reduces the productivity of green technologies and does not effectively achieve sustainable development goals. Environmental issues related to supplier-buyer relationships, environmental decisions, certification, and environmental quality standards [13], [57][58][59][60][61][62][63][64][65] Manufacturing Problems of design, development, and production of ecological products to reduce harmful emissions and waste [66][67][68][69][70] Green logistics Environmental issues related to the sustainable transportation, handling and storage of hazardous materials, inventory management, warehousing, the choice of locations for transport and logistics infrastructure, the use of packaging [11], [70][71][72][73][74][75][76] Reverse logistics Problems of separation of reverse flows (material flows from consumers to sources) into recyclable and waste [14], [77][78][79]…”
Section: Logistic Flows In Green Supply Chainsmentioning
confidence: 99%
“…A literature review [9] showed an increase in the number of MCDM-related publications over the past ten years. MCDMs are actively used to solve various problems in the field of climate change [10], sustainable engineering [9], green logistics [11], GSCM [12,13], reverse logistics [14]. However, the selection of the appropriate MCDM method for a specific situation requires additional research [15].…”
Section: Introductionmentioning
confidence: 99%